Probing the therapeutical potential of conventional and supercritical fluid extract of Zingiber officinale to mitigate ulcer, inflammation, hepatotoxicity and nephron toxicity - Tanweer, Saira; Shehzad, Aamir; Butt, Masood Sadiq; Shahid, Muhammad (Progress in Nutrition, 2018)
Novel health boosting strategies of the millennium have illuminated phytoceutic as one of the promising therapeutic tool to mitigate various health related disorders. In current research work, indigenously grown ginger variety suravi was evaluated for its anti-ulcerogenic, anti-inflammatory, hepato-protective and nephron-defensive potential. For this purpose, nutraceuticalCSE T1 (ethanol extract, 90 min) and nutraceuticalSFE T2 (3300 psi, 50°C, 3 hr) were given to Sprague Dawley rats via oral gavage according to daily intake values (i.e. 3 and 0.3% respectively). In aspirin induced ulcer, ginger extracts showed 38.02% (T1) and 42.9% (T2) reduction for gastric juice volume, 8.45 (T1) and 17.87% (T2) reduction in gastric juice acidity. However, the ulcer index decreased from 2.63 to 1.97 (T1) and 1.68 (T2). In carrageenan induced inflammation, ginger extracts lessen the paw edema from 0.273 to 0.260 and 0.256 in T1 and T2. In CCl4 induced hepatotoxicity, nutraceuticalCSE showed 12.94% reduction in AST, 4.74% in ALP, 10.13% in ALT and 6.56% in bilirubin, however, the nutraceuticalSFE proved 19.99, 14.88, 18.07 and 10.18% reduction in AST, ALP, ALT and bilirubin, respectively. Similarly, in gentamicin induced nephron toxicity, the decrease rate was 8.94, 8.87 and 9.42% for urea, creatinine and uric acid content, accordingly the urea, creatinine and uric acid level lessen to 14.32, 12.10 and 15.94%, correspondingly in T1 and T2.